Sada nástrojů pro (sebe)hodnocení studentů na souvislé praxi - Vystrčilová, Petra (Masaryk University Press, 2022)
Title in English: A Set of Tools for (self) Assessment of Students during Teacher Training An integral component of the preparation of teacher students is a well-thought-out system of reflected teacher training. Long-term experience shows that it is not enough just to increase the amount of practice, but also to reflect the gained experience well in practice. The aim of this publication (respectively, a set of tools for student (self) assessment on teacher training) is to contribute to the improvement of the practical professional training of future teachers at the 1st grade of elementary school.